Ancestralizando : uma atividade lúdica para o ensino de sistemática filogenética no ensino médio - Ribeiro, Rosivânia de Queiróz (2022)
Phylogenetic systematics is an area of science that is based on the concept of ancestry and descent, its main objective is that the biological classification reflects the kinship relationships between living beings. The teaching of phylogenetic systematics is a fundamental foundation for learning other content in biology, but it is often neglected by high school teachers due to the lack of bibliography and activities aimed at this school level. In the literature there are very few didactic activities focused on phylogenetic systematics, and in general, they are aimed at higher education. In this sense, the present work presents a bibliographical research of national and international scope, and the presentation of a new product for the teaching of phylogenetic systematics in high school, in the form of a playful activity. The Ancestralizando game consists of a total of forty-five cards representing different species of living animals and hypothetical ancestors based on the fauna of the State of Mato Grosso. The activity was elaborated from the theoretical contribution proposed in one of the analyzed articles (see RUSSO et al. 2016), where the authors showed the possibility of developing a phylogenetic systematic activity through the observation of morphological characteristics, construction of cladograms and production of more parsimonious phylogenetic trees. In this way, the teacher who applies this product will lead the student to propose hypotheses and test them using a simplified methodology of phylogenetic systematics, characterizing teaching by investigation. The activity produced is accompanied by a manual that describes in detail each step and their respective objectives.